SIGNIFICANCE OF HOUSE DUST MITES IN ATOPIC ALLERGIC PROCESSES - Марина Ивановна Мусина; Владимир Васильевич Климов; Денис Сергеевич Загрешенко; Ярослав Викторович Кухарев; Алина Николаевна Шкатова; Вера Владимировна Пестова; Андрей Владимирович Климов; Михаил Игоревич Слезкин; Мария Александровна Володина; Вануш Агабекович Акобян; Екатерина Вадимовна Овчаренко (Медицина в Кузбассе)
The article has a hybrid nature and includes a review of the modern references on a role of house dust mites in the etiopathogenesis of atopic allergic diseases and original studies of dust accumulation in different rooms (bedrooms, kitchens, student hostels) in three districts of Tomsk with an assessment of the impact on allergic rhinitis patients living in some of these rooms.